JOURNAL OF SETTELMENTS AND SPATIAL PLANNING VOL. 5/2016. - ZOTIC, Vasile (Presa Universitară Clujeană, 2016)
Special Issue no. 5/2016 Planning for Resource Efficient Cities Guest editors: Christian Fertner&Niels Boje Groth Hosted by the EU-FP7 project PLEEC